Molecular Dynamic Simulation of the Porcine Pancreatic Lipase in Non-aqueous Organic Solvents - Chen, Zi-Shi; Wu, Yi-Da; Hao, Jin-Heng; Liu, Yu-Jia; He, Kang-Ping; Jiang, Wen-Hao; Xiong, Mei-Jie; Lv, Yong-Si; Cao, Shi-Lin; Zhu, Jie (Frontiers in Bioengineering and Biotechnology, 2020)
This paper investigates the conformational stability of porcine pancreatic lipase (PPL) in three non-aqueous organic solvents, including dimethyl sulfoxide (DMSO), propylene glycol (PRG), and ethanol (EtOH) through molecular dynamic (MD) simulation. The root mean square deviations (RMSDs), radius of gyration (Rg), solution accessible surface area (SASA), radial distribution function (RDF), hydrogen bond (H-bond), Ramachandran plot analysis, secondary structure, and enzyme substrate affinity of the PPL in the various organic solvents were comparatively investigated. The results showed that the backbone and active pocket RMSD, and hydrophilic ASA of PPL in three solvents increase with the increase in the solvent LogP, while the Rg, hydrophobic ASA, and H-bond between the solvent and PPL decrease. Among the three organic solvents, DMSO acts as a better solvent, in which the PPL can be loose and extended, and retains its native backbone in DMSO compared to PRG and EtOH. Moreover, Ramachandran plot analysis indicated that the PPL structure quality in DMSO was higher than that in PRG and EtOH. Also, the molecular docking results showed that PPL in DMSO exhibited the highest enzyme-substrate affinity.